Stage lighting and pandemic: Aesthetic perspectives on virtual context (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
This article is the result of the curricular component Lighting and Sound by the University of Sorocaba. The aim of the study is to analyze the use of scenic lighting in a new space of representation conditioned by social isolation. The adaptive process of scenic works to the virtual environment has enhanced the lighting as a fundamental aesthetic tool linked to new experiences. Through a field survey and case studies, the theoretical-methodological approach studied how the theater companies Os Satyros and Teatro Oficina Uzyna Uzona established a milestone in the investigation of light in the virtual context, which allied with theatrical practices.
Keywords: lighting; adaptive processes; virtual theater; representation space; social isolation